ANALYSIS OF PROVINCIAL INSPECTORATE ROLE AS INTERNAL GOVERNMENT AUDITOR IN INCREASING THE QUALITY OF LOCAL FINANCIAL REPORTS AND ITS OBJECTIVE IN AUDIT (Case Study Of North Sumatera Government) - Tyus Windi Ayuni (SEAN Institute, 2022)
This study aims to determine this is for knowing the role played by the Inspectorate Body North Sumatra Province for operating function in increasing the quality report finance, for knowing factor obstacles encountered by Inspectorate North Sumatra Province in increasing the quality report finance, and for knowing the sharia audit review in the role of the inspectorate as an internal auditor . technique _ data collection used in this research using Observation Techniques ( Observation ) where the observation is describing the setting being studied, the activities that take place, the people involved in the activity, and the meaning of the event seen from the perspective of those seen in the observed event (Bi Rahmani, 2016). Research results show that the role of the internal auditor of the Inspectorate North Sumatra province is influential and significantly positive in increasing quality report finance government where an Adjusted R square of 0.635 indicates that 63.5% of the role of internal audit is influential to quality report finance government whereas of 36.5% explained by other factors that are not researched in this study.